Gold as an Infl ation Hedge in a Time-Varying Coefficient Framework - Joscha Beckmann; Robert Czudaj (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
This study analyzes the question whether gold provides the ability of hedging against inflation from a new perspective. Using data for four major economies, namely the USA, the UK, the Euro Area, and Japan, we allow for nonlinearity and discriminate between long-run and time-varying short-run dynamics. Thus, we conduct a Markov-switching vector error correction model (MS-VECM) approach for a sample period ranging from January 1970 to December 2011. Our main findings are threefold: First, we show that gold is partially able to hedge future inflation in the long-run and this ability is stronger for the USA and the UK compared to Japan and the Euro Area. In addition, the adjustment of the general price level is characterized by regime-dependence, implying that the usefulness of gold as an inflation hedge for investors crucially depends on the time horizon. Finally, one regime approximately accounts for times of turbulences while the other roughly corresponds to 'normal times'. – – Die vorliegende Studie analysiert die Fragestellung, ob Gold die Möglichkeit der Absicherung gegen Inflationsrisiken bietet aus einem neuen Blickwinkel. Basierend auf Daten für die USA, Großbritannien, die Eurozone und Japan unterscheiden wir mit Hilfe eines Markov-Switching-VECM-Models zwischen langfristigen und zeitvariablen kurzfristigen Dynamiken. Unsere Resultate für den Zeitraum zwischen 1970 und 2011 zeigen zum einen, dass Gold nur teilweise in der Lage ist, als Absicherung gegen zukünftige Inflation zu dienen. Weiterhin wird deutlich, dass die Anpassung des allgemeinen Preisniveaus ans das langfristige Gleichgewicht durch Regime-Abhängigkeit gekennzeichnet ist. Eines dieser Regime bezieht sich auf turbulente Zeiten an den Finanzmärkten, während das andere eher in normalen Zeiten auftritt.
Keywords: C32; E31; E44; 330; Cointegration; gold price; inflation hedge; Markov-switching error correction